Acute patient‐reported outcomes in B‐cell malignancies treated with axicabtagene ciloleucel. (28th February 2021) - Hoogland, Aasha I.; Jayani, Reena V.; Collier, Aaron; Irizarry‐Arroyo, Nathaly; Rodriguez, Yvelise; Jain, Michael D.; Booth‐Jones, Margaret; Hyland, Kelly A.; James, Brian W.; Barata, Anna; Bachmeier, Christina A.; Chavez, Julio C.; et al.
Abstract: Chimeric antigen receptor T‐cell therapy with axicabtagene ciloleucel (axi‐cel) has considerably improved survival in adults with relapsed/refractory large B‐cell lymphoma. This study reports patient‐reported outcomes (PROs) such as quality of life (QOL) and toxicity in the first 90 days after treatment. Hematologic cancer patients treated with axi‐cel ( N = 103, mean age = 61, 39% female) completed SF‐36 or PROMIS‐29 QOL questionnaires prior to treatment and 90 days after. PRO‐Common Terminology Criteria for Adverse Events toxicity items were completed by patients at baseline and 14, 30, 60, and 90 days after treatment. Mixed models examined change in PROs over time. From preinfusion to 90 days later, patients reported improvements in physical functioning, pain, and fatigue ( p s < 0.01), but worsening of anxiety ( p = 0.02). Patient‐reported toxicities worsened by day 14 with improvement thereafter. The five most severe symptoms at day 14 included fatigue, decreased appetite, dry mouth, diarrhea frequency, and problems with concentration. Results indicate improvement in some domains of QOL over time with transient patient‐reported toxicities. Abstract : From pre‐chimeric antigen receptor (CAR) T‐cell therapy infusion to 90 days later, there were significant improvements in physical functioning and reductions in pain and fatigue, but a significant worsening of anxiety. Patient‐reported toxicities worsened by day 14 with improvement thereafter.